The unique compositions of steryl ferulates in foxtail millet, barnyard millet and naked barley. (May 2018) - Tsuzuki, Wakako; Komba, Shiro; Kotake-Nara, Eiichi; Aoyagi, Masato; Mogushi, Hiroyuki; Kawahara, Shuji; Horigane, Akira
Abstract: Although oryzanol in rice bran is one of the most utilised steryl ferulates (SFs, ferulic acid/coumaric acid esters of phytosterol/triterpene alcohol), SFs are also present in other cereals. Thus, we herein report the SF profiles present in various cereals, pseudo-cereals and millets using a high performance liquid chromatography (HPLC) method. The SF contents of whole foxtail millet, whole proso millet, and whole barnyard millet were 28.9, 0.2, and 4.8 mg-oryzanol equivalent/100 g, respectively, indicating that the SF content in whole foxtail millet was about 80% of oryzanol in brown rice. Using an atmospheric pressure chemical ionisation method combined with mass spectrometry (APCI-MS), the SF components from several millets and cereals were identified. It revealed that SFs of whole foxtail millet was composed of stigmastanyl ferulate (73%), stigmastanyl coumarate (10%), and others (17%). Furthermore, SF compositions of whole barnyard millet and naked barley were firstly determined and they were considerably different from those of other cereals. Highlights: Steryl ferulates (SFs) in millets and cereals were analysed by HPLC and APCI-MS. SFs of foxtail millet, barnyard millet and naked barley was firstly identified. SFs content in whole foxtail millet was about 80% that of brown rice. More than 70% of SFs in foxtail millet was stigmastanyl ferulate. Main SF component in naked barley was 24-methylene cycloartanyl ferulate.